Influence of Prior Intense Exercise and Cold Water Immersion in Recovery for Performance and Physiological Response during Subsequent Exercise - Christensen, Peter M.; Bangsbo, Jens (Frontiers in Physiology, 2016)
Athletes in intense endurance sports (eg. 4000-m track cycling) often perform maximally ( 4 min) twice a day due to qualifying and finals being placed on the same day. The purpose of the present study was to evaluate repeated performance on the same day in a competitive setting (part A) and the influence from prior intense exercise on subsequent performance and physiological response to moderate and maximal exercise with and without the use of cold water immersion in recovery (part B). In part A, performance times during 8 World championships for male track cyclists were extracted from the qualifying and final races in 4000-m individual pursuit. In part B, twelve trained cyclists with an average (±SD) V̇O2-peak of 67±5 mL/min/kg performed a protocol mimicking a qualifying race (QUAL) followed three hours later by a performance test (PT) with each exercise period encompassing intense exercise for 4 min preceded by an identical warm-up period in both a control setting (CON) and using cold water immersion in recovery (CWI; 15 min at 15°C). Performance was lowered (P<0.001) from qualification to finals (259±3 vs. 261±3 s) for the track cyclists during World championships in part A. In part B, mean power in PT was not different in CWI relative to CON (406±43 vs. 405±38 W). Peak V̇O2 (5.04±0.50 vs. 5.00±0.49 L/min) and blood lactate (13±3 vs 14±3 mmol/L) did not differ between QUAL and PT and cycling economy and potassium handling was not impaired by prior intense exercise. In conclusion, performance is reduced with repeated maximal exercise in world-class track cyclists during 4000-m individual pursuit lasting 4 min, however prior intense exercise do not appear to impair peak V̇O2, peak lactate, cycling economy or potassium handling in trained cyclists and cold water immersion in recovery does not improve subsequent performance.